Perception of Teachers on Reflective Practice - Pandey, Shiv Ram (Tejganga Darpan, 2024)
This paper focuses on the perception of English teachers on reflective practice and the role of reflection in revealing the reality. The study followed a qualitative research method. 5 English teachers were purposively selected from Tarkeshwor Municipality, Kathmandu. The data was analyzed inductively generating the themes. The findings of the study were that reflective practice is a meditative and thoughtful process, focuses on planning and preparation, recalling and self-assessing process, professional and creative process, process of sharing and strengthening the strength, and motivating, encouraging, enriching and enabling process. It enhances teaching skills and brings changes in teaching learning practices. Teachers have to think, act and reflect tenaciously. As a result teaching learning process is activated and aggrandized. It further presents that every incident has enormous insights to learn through this practice. Eventually, it enhances the professional development of English language teachers.